2020
DOI: 10.3389/fcomm.2020.587465
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Obstacles of Open Access Publishing. A Qualitative Investigation of Individual and Institutional Factors

Abstract: (OA) is an evolving publication model that is heavily supported by politics and science organizations aiming to make scientific knowledge more accessible to a wider audience. Whether it will indeed alter scholarly communication, however, depends on researchers' underlying attitudes, motivations, and needs. Drawing on group discussions and interviews (n = 42), this study explores the perceptions, attitudes and behaviours of researchers towards OA publishing. We focus on researchers in the field of biomedical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…Moreover, most of the COVID-19 articles from SEA were published in paid, open access journals. There are several reasons that may explain this: 1) Article processing charges (APC) remains to be a major obstacle in publishing research in open access journals [26]. Perhaps, more affluent countries like Singapore, Malaysia, and Thailand, which contributed to a lot of COVID-19 publications in SEA, could afford to pay the APC of open access journals; 2) There was a significant increase in the percentage of multiple country publications on COVID-19 research in SEA since the start of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the COVID-19 articles from SEA were published in paid, open access journals. There are several reasons that may explain this: 1) Article processing charges (APC) remains to be a major obstacle in publishing research in open access journals [26]. Perhaps, more affluent countries like Singapore, Malaysia, and Thailand, which contributed to a lot of COVID-19 publications in SEA, could afford to pay the APC of open access journals; 2) There was a significant increase in the percentage of multiple country publications on COVID-19 research in SEA since the start of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…6 Secondary parameters of the transformation metric. Parameters in this figure are taken from Mielke et al 20 (there part of Table 1), and as presented in Haux et al 18 A detailed report on the results of the interviews can be found in Greussing et al, 23 where some major outcomes, presented here, are all taken from:…”
Section: Outcomes Of the Qualitative Study On Drivers And Obstacles O...mentioning
confidence: 99%
“…From July 2017 to February 2018, 42 medical informatics researchers were inter-(researchers with intermediate experience such as postdoctoral researchers), and "senior" (researchers with long experience such as professors or department chairs). Details can be found in Greussing et al23 and here later in ►Table 2. • In addition, a two-tier quantitative study on these drivers and obstacles was designed and conducted, comprising scientific organizations (Module A) and individual researchers (Module B) in medical informatics.…”
mentioning
confidence: 99%
“…Despite agreeing with the OA principles, the majority of researchers at the Arctic University of Norway did not engage in OA for a variety of reasons, including the time-consuming procedure, academics' uncertainty about specific legal, copyright, peer review, and prestige issues, and ambiguity over which version to deposit or self-archive (Mbachi, 2019). While most biomedical and health informatics researchers favor making scientific knowledge freely accessible to everybody, some are hesitant to put this principle into reality by publishing their work in OA journals (Greussing et al, 2020). The primary motivations for researchers to adopt OA publishing are the large readership, impact factor, free access to readers, ability to pay publishing charges, subjective norm and personal innovativeness (Heaton et al, 2019;Massoro and Adewale, 2019).…”
Section: Factors Influencing Researchers' Participation In Oa Publishingmentioning
confidence: 99%